ANALISIS KESEMPATAN KERJA SEKTORAL DI KABUPATEN BANGLI DENGAN PENDEKATAN PERTUMBUHAN BERBASIS EKSPOR - Ayu Pramitha Purwanti, Putu (PIRAMIDA, 2012)
The aim of this study is to analyze the employment of economy sector with full grown potentialwhich will be continuously extended to the economic development of Bangli regency. Theemployment is analyzed by export-based approach. It plays the role of identifying which sectors arebasic and which one are non basic after those sectors undergoing a shift-share analysis. Techniquesof determining those sectors are location quotient (LQ) and employment base multiplier. Basicsectors having ability to create new employment, produce output for local and also export needs.Those will stimulate the Bangli’s economy growth and brings prosperity for all the society.
Keywords: employment, Export-base